Biosimilar competition in European markets of TNF-alpha inhibitors: a comparative analysis of pricing, market share and utilization trends - Car, Elif; Vulto, Arnold G.; Houdenhoven, Mark Van; Huys, Isabelle; Simoens, Steven (Frontiers in Pharmacology, 2023)
Factors like the number of biosimilar competitors and competitive pricing strategies from originator companies may influence price competition and biosimilar uptake. The aim of this study was to analyze multiple facets of biosimilar competition of TNF-alpha inhibitors in Europe by exploring the existence of a biosimilar first-mover advantage, pricing strategies of originator companies, and the evolution in patient access. Sales and volume data on biosimilar and originator infliximab, etanercept, and adalimumab between 2008 and 2020 were provided by IQVIA. Countries included 24 European Union Member States, Norway, Switzerland, United Kingdom, Serbia, and Bosnia and Herzegovina. Sales value was expressed as ex-manufacturer price per defined daily dose (DDD), and volume data were transformed into the number of DDDs per 1,000 inhabitants per day. Descriptive analyses were conducted based on the evolution in price per DDD, trends in biosimilar and originator market shares and utilization trends. Market entry of the first biosimilars of infliximab and adalimumab resulted in a decrease of the volume weighted average price (VWAP) per DDD by 13.6% and 0.9% on average, whilst the second biosimilars resulted in a decrease by 26.4% and 27.3%, respectively. The first and second etanercept biosimilars generated a similar decrease in the VWAP per DDD by 9.3% and 9.1% on average, respectively. Average market share captured by the first biosimilars was at least twice as large as the second biosimilars for all molecules. In addition, sharp reductions in price per DDD of Humira® in most countries indicated a pricing strategy resulting in low uptake of adalimumab biosimilars. Lastly, utilization of infliximab, etanercept, and adalimumab following biosimilar entry increased by an average of 89%, 15%, and 22%, respectively. However, introduction of (multiple) biosimilar competitors did not necessarily translate into increase in treatment access for all three molecules across some European countries indicating a shift in utilization from one molecule towards the other(s). Overall, this study revealed that biosimilar entry results in increased utilization and price reduction, although at a heterogenous rate among TNF-alpha inhibitors. Observed trends in market shares indicate a biosimilar first-mover advantage whereas pricing strategies considered to be anti-competitive can limit market uptake.